Determinants of undergraduates’ academic performance / Cheam Chai Li … [et al.] - Cheam, Chai Li; Yaacob @ Othman, Azmahani; Mohd Fauzi, Noor Zafarina; A Malek @ Abdul, Syazwani (2021)
Education is important to individuals to upgrade one’s standard of living by acquiring knowledge and skills. With educated society and efficient human capital, it would bring about growth, development and prosperity to a country. Thus, universities play a vital role to prepare undergraduates to fulfil the demand for the industries. There are studies on relationship between socio economic variables and academic performance. However, the results are inconsistent. This has prompted the study to examine whether factors such as age, gender, motivation, social activities and institution environment affecting academic performance of undergraduates in UiTM Kelantan. There are 307 sample collected using simple random sampling for logistic regression. The results show that age, motivation and institutional environment are significantly affecting academic performance. The findings are then suggested to the university administrators for future strategic planning.